Archiwum MSW Gruzji – przeszłość, teraźniejszość i przyszłość - Dżachua, Ivane; Łuarsabiszwili, Wladimer; Tuszuraszwili, Omar (Przegląd Archiwalny Instytutu Pamięci Narodowej, 2023)
The fonds that previously comprised three separate historical archives: Committee of the State Security of Georgia, Soviet Police in Georgia and the Communist Party of the Georgian Soviet Socialist Republic constitute the resources of the present Archives of the Ministry of Internal Affairs of Georgia. The authors presented origins of creation of those archives, their fonds, described the content of the most interesting archival fonds and organizational structure of the archives of the Ministry of Internal Affairs. The issues related to popularizing of the archival fonds that is conducted, among others, by publishing the magazine entitled ‘Archival Herald’ in the Georgian and English languages and participation in the production of documentaries have also been discussed in the article. Furthermore, the aspects concerning the international cooperation of the Archives of the Ministry of Internal Affairs of Georgia with foreign organizations, universities and museums as well as research projects conducted by employees have been considered.